n Pedagogiese analise van Alfredo Casella se 11 Pezzi infantile - Brink, Lindie (University of Pretoria, 2017)
One of the most important phases of the piano student's development, is the intermediate phase. It is during this phase that the student must play suitable repertoire that will develop the necessary technical and aural skills and musical maturity in preparation for the advanced piano repertoire. This study was conducted in order to aid the teacher with selecting suitable repertoire for the intermediate piano student. The 11 Pezzi Infantili, composed by the 20th century Italian composer Alfredo Casella, was selected as repertoire suitable for the intermediate piano student. The technical and musical aspects found in these pieces are set out for the teacher to determine whether these pieces are suitable for the student. These aspects will meet the student's level of development and also ensure technical and musical development. Supporting material such as teaching strategies, fingering suggestions, exercises and a background study of the pieces is also provided to assist the teacher during the teaching of these pieces and to ensure better quality teaching. === Die intermediêre fase is van die belangrikste fases in die klavierstudent se ontwikkeling. Die tegniese vaardighede, kritiese luistervermoëns en musikale volwassenheid, nodig vir die speel van gevorderde klavierrepertorium, moet tydens die intermediêre fase deur geskikte repertorium ontwikkel word. Hierdie studie is opgestel en het ten doel om as hulpmiddel vir die klavieronderwyser tydens repertorium-voorskryf vir die intermediêre klavierstudent te dien. Die 20ste eeuse Italiaanse komponis Alfredo Casella se 11 Pezzi Infantili word as geskikte intermediêre repertorium voorgestel. Die tegniese en musikale aspekte van die 11 Pezzi Infantili word uiteengesit, sodat die onderwyser kan assesseer of hierdie stukke vir sy intermediêre student geskik is. Hierdie aspekte is in lieu met die student se vlak van ontwikkeling en sal ook tegniese en musikale ontwikkeling verseker. Onderrigsondersteuning, in die vorm van onderrigstrategieë, vingersettings, begeleidende oefeninge en 'n agtergrondstudie tot die album, word ook voorsien wat die onderwyser as hulpmiddel tydens die onderrig van die stukke kan gebruik om beter gehalte-onderrig te verseker. === Dissertation (MMus)--University of Pretoria, 2016. === Music === MMus === Unrestricted